2022
DOI: 10.1590/0001-3765202220201000
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for monthly rainfall regionalization in southwestern Colombia

Abstract: The knowledge of rainfall regimes is a relevant requirement for many activities such as water resources planning, risk management, agriculture activities management, and other hydrologic applications. The present study has consisted of validating four techniques (one linear, one non-linear, and two hybrids) that allow identifying homogenous regions. We take the monthly rainfall in the Southwestern Colombia (Nariño), an area of 33,268 km 2 characterized by complex topography and local factors that can infl uenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…This region is characterized by not presenting a defined rainfall trend (Guzmán et al, 2014); some areas register high rainfall during the year and, in others, low rainfall, mainly in stations near the Pacific Ocean. These results are consistent with Cerón et al (2021b), who reported a core of high rainfall in the south of the Colombian Pacific (3000 to 7000 mm.year -1 ), and Canchala et al (2022) who reported in the Pacific region of Nariño rainfall ranges from 2500 to 8650 mm.year -1 .…”
Section: Descriptive Statistical Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…This region is characterized by not presenting a defined rainfall trend (Guzmán et al, 2014); some areas register high rainfall during the year and, in others, low rainfall, mainly in stations near the Pacific Ocean. These results are consistent with Cerón et al (2021b), who reported a core of high rainfall in the south of the Colombian Pacific (3000 to 7000 mm.year -1 ), and Canchala et al (2022) who reported in the Pacific region of Nariño rainfall ranges from 2500 to 8650 mm.year -1 .…”
Section: Descriptive Statistical Analysissupporting
confidence: 92%
“…This study chose Ward's method because it has been the clustering technique most used in climate regionalization (Fazel et al, 2018;Canchala et al, 2022). Overall, it outperforms other algorithms in terms of segregation, providing relatively dense groups with minimums within-group variance.…”
Section: Regionalizationmentioning
confidence: 99%
“…The southwest of Colombia (Nariño) is one of the most biodiverse regions of the country and the world, located between 0°21' and 2°40' north latitude and 76°50' and 79°02' west longitude, with approximately 33,268 km2 (Canchala et al, 2020;Ocampo-Marulanda et al, 2022). The Pacific region (14,754 km2) accounts for 52 %, the Andean region (15,466 km2) for 40 % and the Amazon region (3,048 km2) for the remaining 8 % (See Figure 1) (Gobernación de Nariño, 2019).…”
Section: Study Areamentioning
confidence: 99%
“…For this reason, models to estimate ETo have been developed during the last decades, using machine learning techniques such as Artificial Neural Networks (ANN) (Zanneti et al, 2008;Alves et al, 2017;Fonseca et al, 2018;Laqui et al, 2019;Meneses et al, 2020) Autoregressive Integrated Moving Average Model (ARIMA) (Jordan et al, 2008;Gautam and Sinha, Mossad and Alazba, 2016;Bouznad et al, 2020), and Multiple Linear Regression (MLR) (Yirga, 2019). In Colombia, the spatial distribution of climatological stations is uneven due to several factors, such as complex topography (e.g., the Andean Mountain range), areas affected by the armed conflict, and low investment in technological resources, among others (Urrea et al, 2019;Canchala et al, 2022). In southwestern Colombia (Nariño), 76 % of the rainfall stations are in the Andean region, with a density of one station every 470 km2, covering 40 % of the total area of Nariño.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation